Analysis of Designs of Heat Exchangers Used in Adsorption Chillers - Tomasz Bujok; Piotr Boruta; Łukasz Mika; Karol Sztekler (Energies, 2021)
In the face of increasing demands with regard to the share of renewable energy sources in the energy mix, adsorption chillers are becoming a potentially important part of the energy transition. A key component of this type of equipment is the heat exchanger in the adsorption bed, the design of which affects both heat and mass transfer. This study includes an analysis of the geometry and materials used to manufacture such heat exchangers. The geometry analysis is mainly based on the evaluation of the impact of the different dimensions of the exchanger components on heat and mass transfer in the bed. The second part of the study focuses on material-related issues where the main emphasis is on the analysis of the thermal inertia of the exchanger. The paper analyses the latest research on the design of exchangers in adsorption beds, mainly from 2015–2021. Currently, the commonly used SCP and COP coefficients and various test conditions do not provide sufficient information for comparative analysis of adsorption bed heat exchangers, so the authors propose to introduce a new index for the evaluation of heat exchangers in terms of the effect of the design parameters on the energy efficiency of an adsorption chiller.